Factor Affecting Work Engagement, Affective Commitment, And Organizational Citizenship Behavior - Salman Farisi; Muslih; Yudi Siswadi; Muhammad Arif (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
This study examines the effect of transformational leadership on work engagement, affective commitment, and OCB both directly and indirectly. The quantitative design of this study used survey methodology by sending questionnaires to frontline employees in the hospitality industry. One hundred and eighty questionnaires out of 200 questionnaires issued were usable. The data analysis used to test the Structural Equation Model - Partial Least Squares (SEM-PLS) approach is SmartPLS 4.0. The results obtained concluded that transformational leadership, affective commitment, and work engagement affect OCB, transformational leadership affects affective commitment and work engagement, work engagement affects affective commitment, transformational leadership affects OCB through affective commitment, transformational leadership affects OCB through work engagement, and work engagement affects organisational citizenship behaviour through affective commitment. The effect of transformational leadership on OCB of hotel employees in North Sumatra - Indonesia, mediated through affective commitment and work engagement.